The use of spatial terms ‘NEAR’, ‘VERY NEAR, ‘NEXT TO’, ‘SIDE BY SIDE and ‘NEARBY’ in the descriptions of spatial configurations - Ferreira, Maria Engracinda dos Santos; Delazari, Luciene Stamato (Boletim de Ciências Geodésicas, 2019)
Spatial relations are words used to describe the existing relationships between elements present in environments. In the Natural Language, that is, that of the representations present geographical spatial organizations often seen in the daily lives of individuals, the user when reporting their location, uses a significant amount of spatial relations. Consequently, one has the difficulty of defining which of these words are suited to be used in spatial descriptions, in the sense of transmitting spatial information in a clear and precise way. Aiming to foster research in this field, an experiment was carried out with volunteers natives Brazilian Portuguese language in which the use of five spatial relations denoting distances in qualitative terms was sought. The results obtained showed that, although they present similar understandings, the incorrect use of one of these spatial relations can transmit to the receiver of the message an erroneous spatial information. In addition, it was observed a tendency in choosing a specific spatial relation as the distance between the reference elements increases with each other.